BANTAHAN TERHADAP PEMIKIRAN FATIMA MERNISSI: (STUDI KRITIS HADIS ṢAHĪH BUKHĀRI) - Muhamad Faisal (Khulasah : Islamic Studies Journal, 2025)
This research is entitled "Rebuttal to Fatima Mernissi's Thoughts (Critical Study of Hadith Ṣahīh Bukhāri)" This study is based on the justice towards women contained in various religious texts (including hadith) which has begun to be questioned since the presence of the feminist equality movement. Some feminists accuse Islam of being a patriarchal religion that discriminates against and oppresses women. So this study will analyze one of the feminist figures, namely Fatima Mernissi, who conducted a series of criticisms of the authentic hadith of Bukhari. This research is library research, the data sources used in this study are the book of Ṣahīh Bukhāri, and Mernissi's book entitled Woman and Islam: An Historical and Theological Inquiry. Analyzed using the sanad and matan criticism approach so that the results of this study show that, First, Mernissi attacks the personality of Abu Bakrah as one of the narrators in the hadith of female leadership. Abu Bakrah is accused of being a figure who prioritizes political interests in the narration of this hadith, namely being spoken in order to prove it at a critical time. And this is refuted by the hadith in the previous chapter which tells that Abu Bakrah was proven not to side with any side during the civil war not because of political gain. Second, Mernissi gave a series of criticisms of Abu Hurairah. However, scholars agree that the companions were agreed upon for their justice even if the companions were involved in slander/conflict. So that the criticism that was thrown did not invalidate the validity of the companions as transmitters of the hadith. Third, regarding women as bad luck, Mernissi questioned Bukhari why he included the hadith without including the hadith of Aisah as a comparison. Mernissi's question was answered that similar or equivalent hadiths are found in many books. It is even found in Sahih Muslim, so the hadith deserves the predicate muttafaq 'alaih.